Predicting SCC propagation rates and crash morphologies by fast straining metal electrode techniques - Galvele, José Rodolfo (National Association of Corrosion Engineers, 1980)
Fil: Galvele, José Rodolfo Comisión Nacional de Energía Atómica; Argentina